Prevalence of Violence Against Women and Children in Laghouat Forensic Unit - BOUSAID Khedidja; HAMDIS Nesrine; BOUMEDIENE Asma (université ammar telidji laghouat, 2025)
English Abstract Title: Understanding Violence Against Women and Children in Laghouat, Algeria: Prevalence, Profiles, and Predictors of Acute Post-Traumatic Symptoms among Consultants of the Forensic Medicine Department, Hmida Benadjila Hospital. Background: Violence against women and children (VAWC) is a significant public health issue with severe consequences. This study aimed to determine the prevalence and profile of VAWC and identify predictors of acute post-traumatic symptoms among victims consulting the Forensic Medicine Department of Hmida Benadjila Hospital in Laghouat, Southern Algeria, an under-researched region. Methods: A cross-sectional prospective study was conducted over a four-month period. Data were collected from 106 women and 84 child victims of interpersonal violence using a structured questionnaire, including socio-demographics, incident characteristics, perpetrator details, and the PTSD Checklist for DSM-5 (PCL-5) for women or Child PTSD Symptom Scale (CPSS-5) for children to assess early post-traumatic symptoms. Descriptive statistics, bivariate analyses, and multivariate logistic/linear regression models were employed. Results: A high prevalence of interpersonal violence was observed, with 22.0% of all female consultations and 15.3% of child consultations related to VAWC. Among confirmed victims, 89.7% of women and 84.3% of children had experienced interpersonal violence. Significant acute post-traumatic symptoms were present in 56.6% of women (mean PCL-5=33.14) and 46.4% of children (mean CPSS=28.69). For women, multivariate logistic regression (Nagelkerke R²=.413) identified assault at home (OR=6.88), male aggressor (OR=14.47), and trunk injury (OR=15.84) as significant predictors of high early PTSD probability. Higher number of children and living in the marital home predicted greater PCL-5 symptom severity. For children, bivariate analyses highlighted parental substance abuse, divorce, and intrafamilial violence as risk factors for high symptom probability. Multivariate linear regression (Adjusted R²=.299) showed verbal violence, sexual violence, and assault in a public place significantly predicted CPSS symptom severity. Conclusion: Interpersonal violence presents a substantial burden with significant acute psychological sequelae among women and children consulting forensic services in Laghouat. Specific incident characteristics, perpetrator details, and victim circumstances are strong predictors of early post-traumatic distress. These findings underscore the urgent need for targeted screening, trauma-informed interventions, and robust support systems within medico-legal and healthcare settings in the region.
CD-ROM